Material Strategies to Accelerate OPV Technology Toward a GW Technology - Brabec, Christoph; Distler, Andreas; Du, Xiaoyan; Egelhaaf, Hans-Joachim; Hauch, Jens; Heumüller, Thomas; Li, Ning (Advanced Energy Materials, 2020)
With the rise of the solar power century, photovoltaic applications and installations will go beyond the traditional green field power plants and enter any aspect of daily life. Organic photovoltaics (OPVs) demonstrate certified cell efficiencies of over 17% and are expected to contribute to versatile applications powered by solar energy, for instance, applications rely on flexibility, transparency, color management, or integrability. In this work, the progress of OPV technology is briefly reviewed and the material strategies to accelerate OPV technology toward a GW era are analyzed. In addition to the exciting efficiency values achieved for small area devices, there are many important criteria deciding the success of OPV technology. By taking into consideration the synthetic complexity of OPV materials and the operational stability of OPV devices, the industrial figure of merit (i-FoM) is proposed as a fast and reliable method to verify the true potential of a novel material. Furthermore, “soft” key performance indicators are introduced, such as toxicity, flexibility, transparency, processing, which require different development strategies to reflect the potential of OPV technology for specific applications.
CRIS-Team Scopus Importer:2020-10-09
Keywords: device operational stability; organic photovoltaics; organic solar modules; synthetic complexity